The Omission of Accent Marks Does Not Hinder Word Recognition: Evidence From Spanish - Marcet, Ana; Fernández-López, María; Labusch, Melanie; Perea, Manuel (Frontiers in Psychology, 2021)
Recent research has found that the omission of accent marks in Spanish does not produce slower word identification times in go/no-go lexical decision and semantic categorization tasks (e.g., cárcel [prison] = carcel), thus suggesting that vowels like á and a are represented by the same orthographic units during word recognition and reading. However, there is a discrepant finding with the yes/no lexical decision task, where the words with the omitted accent mark produced longer response times than the words with the accent mark. In Experiment 1, we examined this discrepant finding by running a yes/no lexical decision experiment comparing the effects for words and nonwords. Results showed slower response times for the words with omitted accent mark than for those with the accent mark present (e.g., cárcel < carcel). Critically, we found the opposite pattern for nonwords: response times were longer for the nonwords with accent marks (e.g., cárdil > cardil), thus suggesting a “words” bias for accented items in the yes/no lexical decision task. To test this interpretation, Experiment 2 used the same stimuli with a blocked design (i.e., accent mark present vs. omitted in all items) and a go/no-go lexical decision task (i.e., respond only to “words”). Results showed similar response times to words regardless of whether the accent mark was omitted (e.g., cárcel = carcel). This pattern strongly suggests that the longer response times to words with an omitted accent mark in yes/no lexical decision experiments is a task-dependent effect rather than a genuine reading cost.